In vivo Pharmacokinetic Assessment of Lapatinib-Loaded Nanostructured Lipid Carriers Using High-Performance Liquid Chromatography Analysis - P. Naga Haritha, (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Lapatinib, a tyrosine kinase inhibitor used for the treatment of human epidermal growth factor receptor 2-positive breast cancer, suffers from poor aqueous solubility and limited permeability, leading to suboptimal bioavailability. This study aimed to enhance its oral bioavailability through the formulation of lapatinib-loaded nanostructured lipid carriers (L-NSLCs) and to compare their pharmacokinetic performance with a conventional lapatinib suspension (L-SUS). Materials and Methods: L-NSLCs were developed using a lipid-based nanocarrier system and characterized for particle size, zeta potential, and drug entrapment efficiency. A pharmacokinetic study was conducted in male Wistar rats, where both L-NSLCs and L-SUS were administered orally at a dose of 50 mg/kg. Blood samples were collected at pre-determined intervals, and plasma drug concentrations were quantified using a validated high-performance liquid chromatography method with ultraviolet detection, employing gemcitabine HCl as the internal standard. Results: The pharmacokinetic analysis revealed a significant increase in systemic exposure with L-NSLCs compared to L-SUS. The maximum plasma concentration of L-NSLCs was 798.62 ± 26.14 ng/mL, approximately 2.9-fold higher than L-SUS (272.20 ± 16.12 ng/mL). The area under the curve (AUC0-∞) for L-NSLCs (92,903.96 ± 21,646.64 ng·h/mL) showed a marked enhancement compared to L-SUS (9,620.75 ± 781.21 ng·h/mL). In addition, the elimination half-life (t½) of L-NSLCs was prolonged to 59.62 ± 18.62 h, suggesting sustained drug release and extended circulation time. Conclusion: L-NSLCs significantly improved the bioavailability of lapatinib by enhancing its solubility, absorption, and sustained release profile. The lipid-based nanocarrier system offers a promising strategy for optimizing the oral delivery of poorly water-soluble anticancer drugs, potentially leading to better therapeutic efficacy and reduced dosing frequency. Further studies are required to evaluate the long-term stability and clinical benefits of L-NSLCs.